Strategi Pemuridan Pastoral untuk Menguatkan Identitas Iman Generasi Strawberry Berdasarkan Titus 2:1–5 - Stephen, Raymond Hessel (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2025)
This study discusses pastoral discipleship strategies to strengthen the faith identity of the Strawberry Generation based on Titus 2:1–5. This generation is known to have creative potential but is emotionally and spiritually fragile. This phenomenon is influenced by permissive parenting, instant culture, and intensive exposure to digital media. Titus 2:1–5 emphasises the importance of sound teaching, exemplary living, and intergenerational discipleship as the foundation for forming faith identity. This study uses a qualitative method with a literature review, leading to the conclusion that understanding the Strawberry Generation from a sociological and theological perspective shows the need for a holistic approach in understanding the challenges and opportunities of this generation. Faith formation models for the younger generation are often pragmatic and poorly grounded in biblical principles, thus failing to address the emotionally and spiritually fragile challenges of the Strawberry Generation. Through an exposition of Titus 2:1–5 and the application of pastoral discipleship principles, this study formulates a contextual and biblical faith formation strategy. The results provide theological and practical contributions to strengthening the faith identity of the Strawberry Generation and bridging the gap between biblical principles and the needs of the contemporary generation.AbstrakPenelitian ini membahas strategi pemuridan pastoral untuk menguatkan identitas iman Generasi Strawberry berdasarkan Titus 2:1–5. Generasi ini dikenal memiliki potensi kreatif namun rapuh secara emosional dan spiritual. Fenomena ini dipengaruhi oleh pola asuh permisif, budaya instan, serta keterpaparan intensif pada media digital. Titus 2:1–5 menegaskan pentingnya pengajaran sehat, teladan hidup, dan pemuridan lintas generasi sebagai fondasi pembentukan identitas iman. Penelitian ini menggunakan metode kualitatif dengan studi pustaka, maka didapat kesimpulan bahwa adanya pemahaman generasi strawberry dalam perspektif sosiologi dan teologi menunjukkan perlunya pendekatan yang holistik dalam memahami tantangan dan peluang generasi ini. Model pembinaan iman bagi generasi muda sering kali bersifat pragmatis dan kurang berakar pada prinsip biblika, sehingga belum menjawab tantangan generasi strawberry yang rapuh secara emosional dan spiritual. Melalui eksposisi Titus 2:1–5 dan penerapan prinsip pemuridan pastoral, penelitian ini merumuskan strategi pembinaan iman yang kontekstual dan alkitabiah. Hasilnya memberikan kontribusi teologis dan praktis dalam memperkuat identitas iman generasi strawberry serta menjembatani kesenjangan antara prinsip Alkitab dan kebutuhan generasi kontemporer.